Advances in Bioremediation and Phytoremediation 2018
DOI: 10.5772/intechopen.74046
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Constraints of Macrophyte Manipulation for Shallow Lake Management

Abstract: Palic and Ludas lakes are shallow Pannonian lakes, which have undergone rapid eutrophication. High concentrations of nutrients, along with significantly high values of fecal indicators in water samples, indicate that the Palic-Ludas canal, which connects them, contributes to the pollution of the recipient Lake Ludas, a central part of a special nature reserve. In order to improve water quality in the canal and decrease nutrient load of Lake Ludas, it is suggested to use environmentally friendly solutions, so-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Processed water was fed into Lake Palić. At that time Lake Palić was split into four sectors in order to extend retention time (Rudic et al, 2018). The problem is that the nominal volume of Lake Palić is around 10 million m discharged from WWTP is 13 million m 3 per year.…”
Section: History Of Hydrological Disturbancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Processed water was fed into Lake Palić. At that time Lake Palić was split into four sectors in order to extend retention time (Rudic et al, 2018). The problem is that the nominal volume of Lake Palić is around 10 million m discharged from WWTP is 13 million m 3 per year.…”
Section: History Of Hydrological Disturbancesmentioning
confidence: 99%
“…For instance, Tokodi et al (2018) carried out in vitro assessment of a chemical method based on hydrogen peroxide treatment, but they concluded that the application of a dose required for successful cyanobacterial control would also be harmful to other aquatic organisms. On the other hand, Rudic et al (2018) suggested the construction of wetlands, bio-bridges and biobanks, which can improve self-purification process. This method of so-called bio-barriers would be based on autochthonous plants, for example Typha spp, Phragmites spp., Carex spp., etc.…”
Section: Recent Studies and Projects Related To The Lake's Rehabilitamentioning
confidence: 99%
See 1 more Smart Citation